Bilateral and Regional Free Trade Initiatives: Political and Sectoral Issues (2007)
The increasing number of free trade agreements involving both developed and developing countries has raised political and economical concerns, while increasing inconsistencies in international trade law. Non governmental organizations (NGOs) and social movements have strongly criticized these processes as well as the existing unbalanced trade rules resulting from unbalanced power relations between developed, developing and less developed countries (LDCs).